2013
DOI: 10.1364/oe.21.009959
|View full text |Cite
|
Sign up to set email alerts
|

Tabletop single-shot extreme ultraviolet Fourier transform holography of an extended object

Abstract: TitleTabletop single-shot extreme ultraviolet Fourier transform holography of an extended object Permalink https://escholarship.org/uc/item/9m47m0ht

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Using a capillary discharge laser EUV microscopy in transmission mode was demonstrated recently with a single EUV laser pulse, leading to a 54 nm half-pitch spatial resolution and temporal resolution of $1 ns, as reported in [7] and was evaluated in more details using a correlation algorithm, reported in [8]. The same source was also used recently to perform diffraction microscopy of stationary and moving objects with nanometer spatial resolution and nanosecond temporal resolution [9,10]. Such source, although very bright and coherent, both spatially and temporarily, is very adequate for coherent imaging techniques, however, may not be the best choice for full field high resolution microscopy, due to coherence artifacts, presented in high resolution EUV micrographs, [7].…”
Section: Euv Microscopy Based On a Laser-plasma Gas Puff Target Sourcmentioning
confidence: 99%
“…Using a capillary discharge laser EUV microscopy in transmission mode was demonstrated recently with a single EUV laser pulse, leading to a 54 nm half-pitch spatial resolution and temporal resolution of $1 ns, as reported in [7] and was evaluated in more details using a correlation algorithm, reported in [8]. The same source was also used recently to perform diffraction microscopy of stationary and moving objects with nanometer spatial resolution and nanosecond temporal resolution [9,10]. Such source, although very bright and coherent, both spatially and temporarily, is very adequate for coherent imaging techniques, however, may not be the best choice for full field high resolution microscopy, due to coherence artifacts, presented in high resolution EUV micrographs, [7].…”
Section: Euv Microscopy Based On a Laser-plasma Gas Puff Target Sourcmentioning
confidence: 99%
“…Due to the particular dynamics of the generation of the laser, there is a possibility that the direction of the beam slightly changes from shot to shot due to natural fluctuations in the location of the plasma column. Although this is not important for several of the applications demonstrated so far with this laser [19,20,[33][34][35][36][37][38], this is an aspect that must be taken into account when designing a high-resolution instrument like a PSI interferometer. This small variation in the pointing direction of the laser beam imposes a source of error for this particular application that has to be evaluated.…”
Section: Design Of the Interferometermentioning
confidence: 99%
“…Employing such radiation allows to visualize in a direct way through absorption contrast mechanism the flow of the gas, usually investigated with other techniques, such as the interferometry [10]. It was demonstrated that the radiation from a capillary discharge laser operating at a wavelength of = 46.9 nm EUV images permits to obtain a spatial resolution better than 55 nm [11,12], and that the spatial resolution of holographic images [13], employing the same EPJ Web of Conferences 167, 03001 (2018) https://doi.org/10.1051/epjconf/201816703001 PPLA 2017 wavelength, can be improved up to sub-50 nm [14]. A table top EUV laser emitting 13.2 nm wavelength radiation from Ni-like Cd ions was employed for imaging of with a sub-38 nm spatial resolution and a picosecond time resolution [15].…”
Section: Introductionmentioning
confidence: 99%